Tumor Treating Fields (TTFields) demonstrate antiviral functions in vitro, and safety for application to COVID-19 patients in a pilot clinical study - Abutbul, Avraham; Mumblat, Helena; Porat, Yaara; Friedman, Nehemya; Atari, Nofar; Sharabi, Shirley; Nama, Ahmad; Mugahed, Waseem; Kessler, Asa; Kolben, Yotam; Shamir, Reuben Ruby; Manzur, Doron; et al. (Frontiers in Microbiology, 2023)
Coronaviruses are the causative agents of several recent outbreaks, including the COVID-19 pandemic. One therapeutic approach is blocking viral binding to the host receptor. As binding largely depends on electrostatic interactions, we hypothesized possible inhibition of viral infection through application of electric fields, and tested the effectiveness of Tumor Treating Fields (TTFields), a clinically approved cancer treatment based on delivery of electric fields.In preclinical models, TTFields were found to inhibit coronavirus infection and replication, leading to lower viral secretion and higher cell survival, and to formation of progeny virions with lower infectivity, overall demonstrating antiviral activity. In a pilot clinical study (NCT04953234), TTFields therapy was safe for patients with severe COVID-19, also demonstrating preliminary effectiveness data, that correlated with higher device usage.